PRODUCTIVITY OF SUNFLOWER PLANTS UNDER THE INFLUENCE OF PRE-SOWING TREATMENT OF SEEDS AND FOLIAR FEEDING IN THE EASTERN FOREST-STEPPE OF UKRAINE (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Are presented the results of three-year studies on the complex impact of various options for pre-sowing seed treatment and foliar fertilization with various combinations of biological preparations, growth stimulants and complex water-soluble fertilizers on plant productivity and biological yield of seeds of the high-oleic Aurora AM sunflower hybrid are highlighted.Formulation of the problem. In the conditions of the Eastern Forest-Steppe of Ukraine, as a result of global warming, during the last period, the problem of rainfall deficit, long periods without rain and increasing temperature indicators is becoming more and more acute. At the same time, the negative impact of these factors will only grow. In solving this problem, a special role belongs to the pre-sowing treatment of seeds and foliar fertilization with drugs of stimulating and anti-stress action, including those based on beneficial bacteria, mycorrhizal fungi and humic substances.Thus, the scientific substantiation and development of modern sunflower cultivation approaches based on the use of the capabilities of innovative growth stimulators based on humic substances, activators of the soil ecosystem (beneficial bacteria and fungi) and balanced water-soluble mixtures of nutrients are becoming increasingly important, especially in areas of insufficient moisture and high temperatures in the spring and summer period.The purpose of the research was to study the effect of pre-sowing treatment of seeds with various combinations of bacterial, mycorrhiza-forming preparations and growth stimulants based on humic substances, as well as foliar fertilization in different morphological phases with mixture based on growth stimulants with innovative water-soluble fertilizers on growth, development, formation of elements of plant productivity and biological yield of sunflower seeds in the Eastern Forest Steppe of Ukraine.Research methods. The research was conducted in 2022–2024 on the basis of LLC «Alliance Agro» in the Pyryatinsky district of the Poltava region. To solve the tasks, a two-factor field experiment using the method of split plots was laid. The plots of first order were six variants of pre-sowing seed treatment, the second order – seven variants of foliar feeding. The total number of options in the experiments is 42. The area of the sowing and accounting plots of the experiment was 105.0 and 84.0 m2, respectively.Research results. The high efficiency of the researched factors on the formation of higher indicators of plant productivity was established. They were the highest in the variant of pre-sowing treatment of seeds with a mixture of the growth stimulator Blackjack with biological preparation Mycofriend and «PMK-U» in combination with three foliar feeding – during the 12-13th, 35-35th and 51-53rd microphases by the BBCH scale with a solution based on the Blackjack growth stimulator with various brand of complex water-soluble fertilizer Jiva MIX. The number of seeds in the basket in this version was on 95.0 pcs. (11.4 %) more than in the control. Due to the higher values of the mass of 1000 seeds, the difference in the mass of seeds from the basket between this variant and the control was even higher – 14.0 % (59.4 g).The combined effect of pre-sowing seed treatment and foliar fertilization on biological yield of seeds was significantly higher than on the productivity of a single plant because, along with the formation of higher productivity indicators, they also contributed to the preservation of a large number of plants. Thus, in the variant of optimization of pre-sowing treatment of seeds and foliar fertilization (6th variant of factor A i B), the biological yield of seeds on average for three years was 2.82 t/ha and exceeded the control by more than 20.0 %. At the same time, according to the conducted statistical analysis, no significant difference was found both in terms of productivity elements and in terms of biological yield of Aurora AM sunflower hybrid seeds between two and three foliar fertilizing options. Only a trend of growth of these indicators was observed under the condition of carrying out the third feeding.  Conclusions. Thus, on the basis of the statistical processing of the obtained results of the biological yield of seeds, as well as taking into account the lower economic costs due to the refusal of the third foliar feeding, the option of pre-sowing treatment of seeds with a mixture of Mycofriend, Blackjack and «PMK-U» with the following should be considered optimal carrying out two foliar feedings with a mixture of Blackjack growth stimulator with brands of complex, water-soluble fertilizer Jiva MIX developed for different stages of plant development in recommended doses.
Keywords: sunflower; seed treatment; foliar fertilization; growth stimulants; biological preparations; biological yield; crop structure